Financial modeling for business owners and entrepreneurs : developing Excel models to raise capital, increase cash flow, improve operations, plan projects, and make decisions /: developing Excel models to raise capital, increase cash flow, improve operations, plan projects, and make decisions. (2014) - Sawyer, Tom Y
No abstract available